Market-Driven Framework for Guiding Optimisation Decisions in Embedded Systems - Charalampidou, Sofia; Tsolakidis, Paschalis (My University, 2013)
The recent need for web connectivity in the embedded systems domain and in particular the In-Vehicle Infotainment (IVI), has fired discussions about the integration of HTML components in these systems. This need derives from the growing market demands that could be met by more dynamic IVI systems. In this thesis we present a methodological framework that connects the different stakeholders’ interests, for different software quality characteristics of a product, with the optimisation decisions taken during the product development. We validate the proposed framework with an industrial example at Mecel AB, where we extend Mecel’s Populus, an industrial HMI tool suite, with an HTML component that uses the WebKit rendering engine. The purpose of this extension is to enable Populus to render HTML content which is already available through the Internet or content which can be developed and saved locally as HTML pages. In both cases the benefit is the quick and easy access to new content. After extending the product we apply a market driven approach for selecting the optimisation methods and techniques that could be used to enhance the software quality of the integrated product, based on the market needs. We implemented 3 optimisation techniques and we measured the framerate and the changes in lines of code, which were the identified metrics connected with the most important software quality attributes according to the stakeholders. The proposed methodological framework aims to aid developers in similar domains in making market driven optimisation decisions.
Keywords: Data- och informationsvetenskap; Computer and Information Science